2016
DOI: 10.1155/2016/8780764
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the Vulva: A Diagnostic Challenge Case Report

Abstract: Uterine leiomyomas are common and can affect up to 30% of women older than 35 years. Despite this, leiomyomas of the vulva are rare, masquerading, and usually misdiagnosed as Bartholin cyst preoperatively. These smooth muscle tumors are typically painless, solitary, and well circumscribed and can affect female of any age group. We present a case of a 46-year-old female that presented to the clinic with 2-year history of right labial mass and was diagnosed as Bartholin cyst initially. The patient underwent elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Their etiology is still poorly understood, but it is likely that estrogens and progesterone are involved in tumor proliferation, as long as fibroids rarely appear before menarche and often regress after menopause [4]. Immunohistochemical analysis-when performed-reveals estrogen and/or progesterone receptors [1]. Several ectopic localizations have been reported in the literature: vulva, ovaries, urethra, bladder, peritoneum and retroperitoneum [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their etiology is still poorly understood, but it is likely that estrogens and progesterone are involved in tumor proliferation, as long as fibroids rarely appear before menarche and often regress after menopause [4]. Immunohistochemical analysis-when performed-reveals estrogen and/or progesterone receptors [1]. Several ectopic localizations have been reported in the literature: vulva, ovaries, urethra, bladder, peritoneum and retroperitoneum [5].…”
Section: Discussionmentioning
confidence: 99%
“…Vulvar leiomyomas are particularly rare. To our knowledge, only 160 cases have been reported in the literature [1]. Reidel et al found a single fibroid after examining 144 vulvar tumors [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound is the most reliable imaging tool in establishing the diagnosis of uterine and extrauterine leiomyoma [5,12]. Magnetic resonance imaging (MRI) is useful in differentiating benign and malignant lesions in difficult cases [4,5]. A characteristic feature of malignant lesions on MRI is low signal intensity on T2-weighted images [1].…”
Section: Case Presentationmentioning
confidence: 99%